HARNESSING THE POTENTIAL: HIGHER EDUCATION STUDENTS AS CATALYSTS FOR SUSTAINABLE CITIES AND COMMUNITIES - Grewal, Mandeep (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Urbanization has created some of the most alarming challenges in the world, but it has also provided ample opportunities to drive sustainable development (Sustainable Development Solutions Network, 2023). As per the World bank report, two-third of world’s population live in cities and these are the spaces where poverty, hunger, unemployment, inequalities, and environmental degradation coexist with unsustainable consumption and production models that seriously affects the quality of life. Cities are productive areas and centers of innovation; whether through universities, research laboratories, or large companies, new products and services are generated (Sachs, 2015).